2008
DOI: 10.1016/s0079-6123(08)00905-9
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of 5-HT and DA receptors in primate prefrontal cortex: implications for pathophysiology and treatment

Abstract: The prefrontal cortex (PFC) has attracted great research interest because of its involvement in the control of executive functions in both health and disease, and particularly in cognitive functions such as working memory. In schizophrenia, alterations in the PFC are documented at many different levels: molecular, cellular and functional. Furthermore, deficits in cognitive abilities are considered a core feature of schizophrenia and remain a major unmet medical need with respect to this disorder. In order to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 120 publications
2
46
0
Order By: Relevance
“…Consistent with recent calls to acknowledge the 5-HT system when investigating the effects of dopaminergic drugs (de Almeida et al, 2008), we further found that the COMT ϫ Substance interaction was potentiated in carriers of the less functional 5-HTTLPR variant, which is linked to reduced 5-HT uptake (Lesch et al, 1996). The 5-HT system is a relevant modulator of dopaminergic processes and influences mPFC DA release induced by D2 receptor antagonists (Kuroki et al, 1999).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with recent calls to acknowledge the 5-HT system when investigating the effects of dopaminergic drugs (de Almeida et al, 2008), we further found that the COMT ϫ Substance interaction was potentiated in carriers of the less functional 5-HTTLPR variant, which is linked to reduced 5-HT uptake (Lesch et al, 1996). The 5-HT system is a relevant modulator of dopaminergic processes and influences mPFC DA release induced by D2 receptor antagonists (Kuroki et al, 1999).…”
Section: Discussionsupporting
confidence: 88%
“…The 5-HT system is a relevant modulator of dopaminergic processes and influences mPFC DA release induced by D2 receptor antagonists (Kuroki et al, 1999). Glutamatergic pyramidal neurons presumably involved in ERN generation (Ullsperger, 2010) receive inputs not only from dopaminergic but also from serotoninergic fibers and GABAergic interneurons, which receive projections from raphe nuclei serotoninergic neurons (de Almeida et al, 2008). Of relevance, the less functional 5-HTTLPR alleles have previously been linked to increased risk for depression after stressful life events (Caspi et al, 2003), which also affect the DA system (Pruessner et al, 2004), and for schizophrenia when individuals also carry the Val allele of the COMT Val158Met polymorphism (Borroni et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In support of our findings, another line of evidence suggests that 5-HT1A receptor agonists increase dopamine release in the PFC (for review: de Almeida et al, 2008). Therefore, the stronger Ne in homozygous carriers of the À1019 C allele may be explained by stronger stimulating effects on the DA system in carriers of the CC genotype compared to the CG and GG genotypes.…”
Section: Discussionsupporting
confidence: 87%
“…The DA system is crucially modulated by the serotonergic system within the prefrontal cortex (PFC) (for review: de Almeida et al, 2008). These interactions may form the neurobiological basis of the observed influence of the serotonergic system on error processing functions that has been shown in studies examining depression (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation